Pengaruh Stres Kerja dan Lokus Kendali terhadap Kinerja Guru - Budiyarti, Nelly; Handayani, Henni Rahayu; Abadi, Hadi Prana (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This research aims to determine the effect of work stress and locus of control on teacher performance. This research targets teachers at SMA Negeri 15 South Tangerang City with a saturated sample of 60 teachers. The data collection technique uses a questionnaire with measurement scale is Likert scale. The data analysis technique used is multiple linear regression analysis with the help of SPSS software. The research results show that 1). Work stress and locus of control simultaneously have a positive effect on teacher performance; 2) work stress partially has a positive effect on teacher performance; and 3) locus of control partially does not have a positive effect on teacher performance. It is hoped that this research can contribute to improving teacher performance through controlling work stress by managing the division of teacher tasks based on teacher competence and time allocation, and increasing locus of control.